Potential of five legume species as green manure in the highland area of San Luis Potosí, Mexico - Zavala-Sierra, Daniela; Rodríguez-Ortiz, Juan Carlos; Alcalá-Jáuregui, Jorge A.; Ruiz-Espinoza, Francisco H.; González Mancillas, Rigoberto; Rodríguez-Fuentes, Humberto; Delgado Sánchez, Pablo (Revista Mexicana de Ciencias Agrícolas, 2018)
The green fertilizers (AV) are an alternative to improve the fertility and conservation of agricultural soils in semi-arid zones. For this reason, the potential of five legume species as AV in the highlands of San Luis Potosi, Mexico was evaluated. The study species were: 1) black dolichos beans (Lablab purpureos); 2) beans brown dolichos (Lablab purpureos); 3) red dolichos beans (Lablab purpureos); 4) yorimon bean (Vigna unguiculata); and 5) chickpea (Cicer arietinum). The trial was carried out under a randomized block design with three repetitions. In the stage of flowering of each species the evaluation was carried out. The variables that were measured were: biomass, carbon capture, carbon footprint, nitrogen in plant and C/N ratio. The results indicate that Dolichos red was the most outstanding in biomass production (6.5 t ha-1), carbon capture (2.97 t ha-1) and carbon footprint (-4.3 t ha-1). Cicer arietinum excelled in concentrating N in its tissues (2.03, 1.47 and 1.87% in aerial part, root and whole plant) and could contribute to the soil up to 83 kg ha-1 N. Cicer sp., Had the lowest C/N ratio with 24.12, which would have a faster mineralization than the other species. In conclusion, the five species have the potential to be used as AV in the study area and are an important alternative to improve agricultural soils and the environment.
Keywords: Lablab, Cicer, Vigna, carbon, nitrogen.